MAS architecture and knowledge model for vehicles data communication - Emmanuel ADAM; Emmanuelle GRISLIN-LE STRUGEON; René MANDIAU (Advances in Distributed Computing and Artificial Intelligence Journal, 2012)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false EN-US JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> Completely autonomous vehicles in traffic should allow to decrease the number of road accident victims greatly, and should allow gains in terms of performance and economy. Modelling the vehicles interaction, and especially knowledge sharing, is one of the main challenges to optimize traffic flow with autonomous vehicles. We propose in this paper a model of knowledge communication between mobile agents on a traffic network. The model of knowledge and of interaction enables to propagate new knowledge without overloading the system with a too large number of communications. For that, only the new knowledge is communicated, and two agents communicate the same knowledge only once. Moreover, in order to allow agents to update their knowledge (perceived or created), a notion of degradation is used. A simulator has been built to evaluate the proposal, before to implement it in mobile robots. Some results of the simulator are proposed in this article. <!--EndFragment-->